What one needs to know for the assessment of timber structures - Cruz, H. (2009)
The assessment of old timber structures is normally a great source of problems for building interventors and a frequent justification for integral replacement of structures that would otherwise be kept in service. It requires understanding the original structural system behaviour, the estimation of strength and stiffness properties of the timber in use, the evaluation of individual timber members’ quality and effective cross section dimensions. Due to the natural variability of timber, unknown load and environment history, and common biological damage, assumptions have to be made, frequently with a high degree of uncertainty. This paper discusses the common approach in the assessment of timber structures in service and tries to identify advances, problems, knowledge gaps and research needs related to this activity.